Ochthebius hivae (Coleoptera: Hydraenidae) from western Iran, a new species of the O. metallescens group with remarkable aedeagal variability - Jäch, Manfred; Irani, Elham; Delgado, Juan A. (Zootaxa, 2013)
Ochthebius hivae is described from western Iran (Ilam and Khuzestan Provinces). It belongs to the O. metallescens Rosenhauer, 1847 species group. The aedeagal distal lobe of this species is remarkably variable.